2010
DOI: 10.1111/j.1440-1746.2009.06214.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of Helicobacter pylori infection and gastrointestinal diseases in the past 17 years

Abstract: Over the 17-year period, accompanying the decreasing prevalence of H. pylori infection, the age-adjusted prevalence of peptic ulcer and gastric cancer decreased, but that of reflux esophagitis increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 11 publications
8
46
0
1
Order By: Relevance
“…We also have to consider that the widespread eradication of H. pylori may have a marked effect on the decrease of peptic ulcer associated with H. pylori infection (8) . Giving support to our findings there are many studies that identified similar results (2,7,14,15,16,18) . On the other hand, it is not a worldwide phenomenon, because in some others studies H. pylori still remains highly associated to PUD (3,22,24) .…”
Section: Discussionsupporting
confidence: 88%
“…We also have to consider that the widespread eradication of H. pylori may have a marked effect on the decrease of peptic ulcer associated with H. pylori infection (8) . Giving support to our findings there are many studies that identified similar results (2,7,14,15,16,18) . On the other hand, it is not a worldwide phenomenon, because in some others studies H. pylori still remains highly associated to PUD (3,22,24) .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of H. pylori infection significantly decreased from 70.5% to 52.7%. The decrease in prevalence of peptic ulcer in 2005 was 34%, of GC 56% (effect mainly in men) of the prevalence in 1988 [27]. However, reflux esophagitis showed a 4.8-fold increase in the same time period.…”
Section: H Pylori As High Risk Indicatormentioning
confidence: 95%
“…In economically developed countries, the decreasing incidence of gastric cancer, especially intestinal type, is suggested to be related to environmental factors, such as H. pylori infection. [22][23][24] However, data concerning both hepatoid adenocarcinoma and H. pylori infection were unavailable before this study. In this study, four surgical specimens were positive for H. pylori.…”
Section: Discussionmentioning
confidence: 99%